Pengenalan Nilai-nilai Kepemimpinan Nyi Ageng Serang sebagai Upaya Membangun Karakter Generasi Penerus Bangsa di Kabupaten Kulon Progo, DIY. - Wulandari, Nuryuana Dwi; Lestari, Siska Nurazizah; Pambudi, Wahyu; Subaryana, Subaryana; Nugraha, Nugraha; JB. Yurahman, JB. Yurahman; Astuti, Anita Dewi; Agung, Rendi Marta; Dewantari, Nuryunita; Arrazaq, Naufal Raffi; Ningrum, Azizah Puspa; Nurtanti, Azizah (Medan Resource Center, 2023)
This article aims to discuss the introduction of Nyi Ageng Serang's leadership values as an effort to build the character of the nation's next generation. Building character according to the character of the Indonesian nation is very important considering the increasingly development of technology that will affect the character of the nation's next generation. For this reason, the Community Service Team collaborated with schools in the Special Region of Yogyakarta to introduce local heroes who were made National heroes, one of which was Nyi Ageng Serang. The stages carried out in community service begin with observation, coordination, execution and evaluation. This community service uses lecture and discussion methods. From this community service, students who will become the next generation of the nation are starting to have an interest in getting to know and deepen local heroes who have become national heroes such as Nyi Ageng Serang.